2008
DOI: 10.1128/ec.00138-08
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule Motor Protein Kar3 Is Required for Normal Mitotic Division and Morphogenesis in Candida albicans

Abstract: The kinesin-related protein Kar3 is a minus end-directed molecular motor that plays a multifunctional role in microtubule-directed nuclear movement. Previously, it was shown that Candida albicans Kar3p is critical for nuclear fusion during mating as kar3 mutants were defective in karyogamy. In this study, we confirm that Kar3p is required for nuclear congression in mating but that neither Kar3p nor the dynein motor protein Dyn1p is required for nuclear migration in the mating projection prior to cell fusion. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 65 publications
4
31
0
Order By: Relevance
“…This led to the hypothesis that increased rates of white-opaque switching were a direct consequence of longer generation times. We subsequently examined several other slow growing strains in the laboratory, including a strain lacking the molecular motor KAR3, as well as a strain expressing fluorescently labeled histone (H2B) and tubulin (Tub2) proteins (Sherwood and Bennett, 2008). Both of these strains exhibit a significant delay in cell generation times, growing at least 10% slower than SC5314 (see Sherwood and Bennett, 2008; Table 3).…”
Section: A Connection Between White-opaque Switching and Cellular Gromentioning
confidence: 99%
See 2 more Smart Citations
“…This led to the hypothesis that increased rates of white-opaque switching were a direct consequence of longer generation times. We subsequently examined several other slow growing strains in the laboratory, including a strain lacking the molecular motor KAR3, as well as a strain expressing fluorescently labeled histone (H2B) and tubulin (Tub2) proteins (Sherwood and Bennett, 2008). Both of these strains exhibit a significant delay in cell generation times, growing at least 10% slower than SC5314 (see Sherwood and Bennett, 2008; Table 3).…”
Section: A Connection Between White-opaque Switching and Cellular Gromentioning
confidence: 99%
“…We subsequently examined several other slow growing strains in the laboratory, including a strain lacking the molecular motor KAR3, as well as a strain expressing fluorescently labeled histone (H2B) and tubulin (Tub2) proteins (Sherwood and Bennett, 2008). Both of these strains exhibit a significant delay in cell generation times, growing at least 10% slower than SC5314 (see Sherwood and Bennett, 2008; Table 3). In addition, we found that white colonies from ⌬/⌬kar3 and H2B/Tub2-labeled strains also switched to opaque at high frequency (25 and 22%, respectively; Table 4), thereby supporting a connection between cell growth and switching.…”
Section: A Connection Between White-opaque Switching and Cellular Gromentioning
confidence: 99%
See 1 more Smart Citation
“…albicans Kar3 (CaKar3) is a kinesin-14 family member that has been shown to function in mitotic division and is critical for hypha formation and nuclear fusion during mating (9,11). Its homolog in Saccharomyces cerevisiae has similar functions in mitosis and mating that are enabled by interactions with two kinesinlike proteins: S. cerevisiae Cik1 (ScCik1) and ScVik1 (12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Hyphae are the invasive form and are important for virulence during systemic infections as well as for biofilm formation (1,5,6). In all of these morphological states, microtubuleassociated motor proteins play major roles in microtubule cytoskeleton remodeling, nuclear movements, chromosome segregation, and cargo transport (7)(8)(9). This provides a rationale for their use as novel targets for antifungal drugs (10).…”
mentioning
confidence: 99%